Simaksaja: visual novel game with TyranoBuilder software for Islamic moderation in elementary schools - Ibda, Hamidulloh; Aniqoh, Aniqoh; Muntakhib, Ahmad; Mar’atussolichah, Mar’atussolichah; Fadhilah, Trifka Dila; Rakhmawati, Nurma Febri (Institute of Advanced Engineering and Science, 2024)
The study aims to determine the development, feasibility, and effectiveness of the Simaksaja game. The research was conducted due to the lack of development of digital games based on religious moderation in elementary schools. This research and development refer to the analysis, design, development, implementation, and evaluation (ADDIE) type of Dick, Carey, and Carey model. Data were collected through student and teacher needs analysis, media expert and material expert validation tests, effectiveness tests, structured observation, in-depth interviews, and document study. The research subjects were 46 teachers and 46 students for the needs analysis and effectiveness test in 2 schools in the District and City of Magelang. The research findings stated that the game features character-driven material, the introduction of the characters Ning and Gus, and quizzes. Based on the feasibility test, the game expert scored 72%, the moderation material expert 88%, and the Aswaja Annahdliyah material expert 72%, and it was feasible to use. This game is effective based on the effectiveness test in two elementary schools, scoring 80% from the educators’ response and 87% from the students’ response. The novelty of the research is that the TyranoBuilder game contains religious moderation characters, Aswaja Annahdliyah, Pancasila student profile, and Rahmatan Lil Alamin student profile.